2020
DOI: 10.1371/journal.pone.0232510
|View full text |Cite
|
Sign up to set email alerts
|

Rescue oxygenation success by cannula or scalpel-bougie emergency front-of-neck access in an anaesthetised porcine model

Abstract: In the obese, the evidence for the choice of the optimal emergency front-of-neck access technique is very limited and conflicting. We compared cannula and scalpel-bougie emergency front-of-neck access techniques in an anaesthetised porcine model with thick pretracheal tissue. Cannula and scalpel-bougie cricothyroidotomy techniques were performed in 11 and 12 anaesthetised pigs, respectively. Following successful tracheal access, oxygenation was commenced and continued for 5 min using Rapid-O2 device for cannul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…As in adults, a surgical eFONA with scalpel is recommended: in the absence of an ENT surgeon, rapid sequence surgical tracheostomy should be preferred to access the trachea for emergencies in children under 8 years of age [ 86 ]. For children older than 8 years, we prefer a scalpel bougie technique over a needle technique [ 87 , 88 , 86 ]. There are no other special recommendations for changes in technique in children with aerosol-transmitted viral disease.…”
Section: Pediatric Airway Managementmentioning
confidence: 99%
“…As in adults, a surgical eFONA with scalpel is recommended: in the absence of an ENT surgeon, rapid sequence surgical tracheostomy should be preferred to access the trachea for emergencies in children under 8 years of age [ 86 ]. For children older than 8 years, we prefer a scalpel bougie technique over a needle technique [ 87 , 88 , 86 ]. There are no other special recommendations for changes in technique in children with aerosol-transmitted viral disease.…”
Section: Pediatric Airway Managementmentioning
confidence: 99%
“…Another study conducted by Rees et al 11 on palpable neck anatomy in ovine models yielded similar results, in which the cannula technique was quicker and more successful than the scalpel-bougie technique. Conversely, Umek et al 12 found no difference in success and time between cannula and scalpel-bougie cricothyrotomy in porcine models. However, the study participants made a transverse skin incision followed by 2-finger blunt tissue dissection before making a transverse stab through the cricothyroid membrane for the scalpel-bougie technique.…”
Section: Discussionmentioning
confidence: 95%
“…Another study conducted by Rees et al 11 on palpable neck anatomy in ovine models yielded similar results, in which the cannula technique was quicker and more successful than the scalpel-bougie technique. Conversely, Umek et al 12 found no difference in success and time between cannula and scalpel-bougie cricothyrotomy Data are presented as number (proportion) and 95% CI. Comparison of the success rates using a mixed-effects logistic regression.…”
Section: Discussionmentioning
confidence: 96%
“…In human clinical practice, this technique has a very high failure rate [18] and is not the primary option recommended for CICO as surgical techniques are superior [2]. An experimental study in pigs found only a 20% success rate at delivering rescue oxygenation, citing frequent kinking or displacement of the catheter as reasons for failure [19]. This may explain the outcome of both cases that underwent CPA with a cannula tracheostomy in place (cases 1 and 3).…”
Section: Discussionmentioning
confidence: 99%